2005
DOI: 10.1007/s11119-005-3679-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of Irrigated Corn Yield in Relation to Field Topography and Soil Chemical Characteristics

Abstract: Abstract. Corn yield, topography and soil characteristics were sampled on a 26 ha area of a centre pivot irrigated cropland. The aim of the study was to determine relationships between corn yield, field topography and soil characteristics. The study was carried out in the Alentejo region of Portugal. Corn yield was measured with a combine harvester fitted with a grain-flow sensor and positioned by means of the Global Positioning System (GPS). A grid-based digital elevation model (DEM) with 1-m resolution was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 10 publications
3
12
0
2
Order By: Relevance
“…thus, the semivariograms explained most of the variation in experimental data. the spherical model was fitted for corn yield, which agreed with the result obtained by Silva & alexandre (2005). a strong spatial dependence was observed for corn yield (table 4).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…thus, the semivariograms explained most of the variation in experimental data. the spherical model was fitted for corn yield, which agreed with the result obtained by Silva & alexandre (2005). a strong spatial dependence was observed for corn yield (table 4).…”
Section: Resultssupporting
confidence: 86%
“…Montezano et al (2006) observed a positive correlation between corn yield and clay, oM and boron content, and a negative correlation for the sand, copper, manganese and zinc content in a Rhodic hapludox under no-tillage. Silva & alexandre (2005) found a positive correlation between corn yield and the CeC, Ca 2+ and K + contents in soils arising from calcareous deposits. the h + al content showed a negative correlation with corn yield, which was expected because higher concentrations of h + al content increase soil acidity.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…These potential yield variations can be directly linked to the topography and consequently to the water conditions of the plant, with limited water stress during the dry year in the lower part of the field and water logging during the rainy year. The influence of the topography was previously shown by Marques Da Silva and Alexandre (2005), who proposed topographical indices to help in sitespecific management for delineating areas where crop yields are more sensitive to extreme water conditions. Our results confirmed the observations obtained by yield monitoring; Eghball and Varvel (1997) and Lamb et al (1997) showed that, under rainfed conditions, the temporal variability of yields was more dominant than spatial variability, indicating that spatial patterns in grain yields were greatly affected by yearly climatic conditions, particularly by year-to-year changes in seasonal water supply.…”
Section: Discussionmentioning
confidence: 82%